Odyssey Self Reflection - Betta Fish / Faculty of Art and Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif (Perpustakaan Tun Abdul Razak, PTAR Universiti Teknologi Mara Cawangan Sarawak, 2021)
My idea is about the uniqueness of Betta Fish and these artworks were focusing on the pattern and colour of Betta Fish. The artworks specifically highlighted the beauty of Betta fish, thus the use of warm and cool colours. The sculpture was applied ready-made materials such as frame, milk can and PVC pipe. The technique for producing printmaking were intaglio and stencil